PTRF/Cavin-1 as a Novel RNA-Binding Protein Expedites the NF-κB/PD-L1 Axis by Stabilizing lncRNA NEAT1, Contributing to Tumorigenesis and Immune Evasion in Glioblastoma - Yi, Kaikai; Cui, Xiaoteng; Liu, Xing; Wang, Yunfei; Zhao, Jixing; Yang, Shixue; Xu, Can; Yang, Eryan; Xiao, Menglin; Hong, Biao; Fang, Chuan; Kang, Chunsheng; et al. (Frontiers in Immunology, 2022)
Background: Immunotherapy, especially checkpoint inhibitors targeting PD-1 or PD-L1, has revolutionized cancer therapy. However, PD-1/ PD-L1 inhibitors have not been investigated thoroughly in glioblastoma (GBM). Studies have shown that polymerase 1 and transcript release factor (PTRF/Cavin-1) has an immune-suppressive function in GBM. Thus, the relationship between PTRF and PD-L1 and their role in immune suppression requires further investigation in GBM. Methods: We used public databases and bioinformatics analysis to investigate the relationship between PTRF and PD-L1. We next confirmed the predicted relationship between PTRF and PD-L1 in primary GBM cell lines by using different experimental approaches. RIP-Seq, RIP, ChIP, and qRT-PCR were conducted to explore the molecular mechanism of PTRF in immunosuppression. Results: We found that PTRF stabilizes lncRNA NEAT1 to induce NF-κB and PD-L1 and promotes immune evasion in GBM. PTRF was found to correlate with immunosuppression in the public GBM databases. PTRF increased the level of PD-L1 in primary cell lines from GBM patients. We carried out RIP-Seq of GBM cells and found that PTRF interacts with lncRNA NEAT1 and stabilizes its mRNA. PTRF also promoted the activity of NF-κB by suppressing UBXN1 expression via NEAT1 and enhanced the transcription of PD-L1 through NF-κB activation. Finally, PTRF promoted immune evasion in GBM cells by regulating PD-1 binding and PD-L1 mediated T cell cytotoxicity. Conclusions: In summary, our study identified the PTRF-NEAT1-PD-L1 axis as a novel immune therapeutic target in GBM.